Water for injections: Global trends in pharmacopoeial quality assessment and Russian expert practice - S. M. Sukhanova; A. A. Semenov; N. M. Minaeva (Биопрепараты: Профилактика, диагностика, лечение)
INTRODUCTION. High quality standards for sterilised water for injections arise from the need to guarantee the safety and effectiveness of injectable medicines, especially biologicals, since the presence of impurities in the solvent (mainly microbial contaminants, endotoxins, and heavy metals) can lead to serious adverse drug reactions. Therefore, it is important to determine the most promising approaches to assessing the quality of water for injections to develop the regulatory requirements for the Eurasian Economic Union (EAEU).AIM. This study aimed to analyse key trends in the quality assessment of water for injections used as a solvent for medicinal products.DISCUSSION. This study involved a retrospective comparison of the quality control requirements for water for injections established by the world’s major pharmacopoeias, including the State Pharmacopoeia of the Russian Federation, the United States Pharmacopeia, the Japanese Pharmacopoeia, the European Pharmacopoeia, the British Pharmacopoeia, the  Pharmacopoeia, and the Pharmacopoeia of the People’s Republic of China. Additionally, the comparison included recommendations by the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use and the Pharmacopoeia Discussion Group. The past decade witnessed significant changes in the approach of international pharmacopoeias to the control of organic and inorganic impurities in water for injections, both in terms of analytical procedures and in terms of the number of tests required. According to the comparison, the most significant changes to the quality control requirements for sterilised water for injections in the finished dosage form were introduced by the European Pharmacopoeia in 2024. The authors considered the possibility to streamline the quality control procedure by reducing the number of tests and replacing the currently required ten qualitative tests for inorganic impurities with a single quantitative determination of electrical conductivity. This article describes the replacement of the test for organic impurities with a quantitative test for total organic carbon. Furthermore, this article presents the quality control results obtained at the Scientific Centre for Expert Evaluation of Medicinal Products of the Ministry of Health of the Russian Federation for 148 batches of sterilised water for injections supplied with biologicals produced by 38 Russian and international manufacturers.CONCLUSIONS. The current requirements of the revised monograph for water for injections and sterilised water for injections of the European Pharmacopoeia (07/2024:0169) may inform drafting a relevant compendial standard for the EAEU and updating the monograph for water for injections of the State Pharmacopoeia of the Russian Federation. This will help optimise the quality control procedures, increase the speed and accuracy of testing, and reduce financial and labour costs, which will improve the quality of the solvent and the associated medicinal products. The adoption of these requirements will contribute to pharmacopoeial harmonisation by setting uniform quality control criteria for water for injections for both national and international manufacturers, which will reduce regulatory barriers and facilitate the entry of the solvent dosage form into international markets.